2001
DOI: 10.1128/jcm.39.12.4440-4444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BACTEC Mycobacteria Growth Indicator Tube (MGIT 960) Automated System for Drug Susceptibility Testing of Mycobacterium tuberculosis

Abstract: The reliability of the BACTEC MGIT 960 system, an automated version of the Mycobacteria Growth Indicator Tube (MGIT), for antimicrobial susceptibility testing of Mycobacterium tuberculosis was evaluated on 78 clinical isolates. Rifampin (RMP), isoniazid (INH), streptomycin (SM), and ethambutol (EMB) were tested at the following concentrations: 1.0 g/ml for RMP, 0.1 and 0.4 g/ml for INH, 1.0 and 4.0 g/ml for SM, and 5.0 and 7.5 g/ml for EMB. Results were compared with those obtained by the BACTEC 460 TB radiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 27 publications
7
83
2
2
Order By: Relevance
“…The time to report Bactec MGIT indirect DST from positive cultures varied from 6 to 10 days, which is concordant with many earlier reports (1,2,7,20). This time to report varies depending on many factors, including variability in the standard procedure followed in a laboratory, patient population, and prevalence of drug resistance.…”
Section: Discussionsupporting
confidence: 79%
“…The time to report Bactec MGIT indirect DST from positive cultures varied from 6 to 10 days, which is concordant with many earlier reports (1,2,7,20). This time to report varies depending on many factors, including variability in the standard procedure followed in a laboratory, patient population, and prevalence of drug resistance.…”
Section: Discussionsupporting
confidence: 79%
“…In studies described in previously published papers, discrepancies between results from the evaluated methods were resolved by means of reanalysis with the two methods (12) or with the proportion method on Löwenstein-Jensen slants (3)(4)(5)22) or in Middlebrook 7H11 agar (19). However, our study is unique in the arbitration of discrepant results; we reanalyzed the strain using the three systems, determined the MIC, and characterized some of the molecular resistance determinants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that its sensitivity varies between 80% and 98.1% and its specificity varies between 89.6% and 100%. The MGIT 960 system is also used extensively for the antibiotic sensitivity in vitro test, and data obtained from different studies have shown that this system is a reliable and effective way to quickly determine the sensitivity to anti-tuberculosis drugs of a tubercular isolated strain [11].…”
Section: Isolation and Culturementioning
confidence: 99%